Analisis Framing Pemberitaan Tragedi Kanjuruhan di Media Online - Dicky Irawan Taufiq; Hamid Arifin (Universitas Sebelas Maret (UNS), 2024)
The Kanjuruhan tragedy has captured the world's attention as one of the most heart- wrenching incidents in the history of global football, resulting in numerous casualties. This event is considered to have high news value by the media, as football is also one of the closest forms of entertainment to society. This research aims to analyze how the news framing is presented by the online media portal Narasi.tv through its program called